Molecular disturbances of erythrocytes membrane during pathology of different genesis are the typical reaction of the organism: contours of the problem - V. V. Novitsky; N. V. Ryazantseva; Ye. A. Stepovaya; T. S. Fyodorova; Ye. B. Kravets; V. V. Ivanov; T. V. Zhavoronok; N. Yu. Chasovskikh; O. M. Choudakova; V. N. Butusova; N. M. Yakovleva (Бюллетень сибирской медицины, 2006)
General patterns and peculiarities of changes in structure and function of red blood cell’s membrane during pathology of different genesis are considered in the article. Based on literature data and our own investigations one concludes concerning presence of typical molecular disturbances of erythrocyte’s membrane in different diseases. But general character of molecular modification of plasmatic membrane during pathology of different genesis is controversial. Universal mechanisms of structural and functional modification of structure and function of cells’ membrane are considered in details.